Colonial Print Culture: Sundanese Book Publishing in the Dutch East Indies in the Early Twentieth Century - Mikihiro Moriyama (Lembaran Sejarah, 2021)
The indigenous book publishing business for Sundanese-speaking communities started in the early 20th century, when the nationalist movement was set in motion. The modern school system had continued to spread in colonial society from the mid–19th century. The more education spread, the more literate people there were among the indigenous population. The indigenous book publishing business responded to the demands of this newly-emerging readership. Book publishing finally turned into a business by the 1920s. It seems to have provided distinctive readings from those provided by Balai Poestaka. The indigenous publishers played a supplemental role in nurturing print culture in the colonial context. Both government and private indigenous publishers contributed to promote modern readership and a colonial print culture. The book publishing and print culture in regional languages like Sundanese were nurtured in the colonial period and grew to constitute a medium to decolonize knowledge and knowledge culture.